Nitric Oxide: Target for Therapeutic Strategies in Alzheimer's Disease - P. Fernandez, A.; Pozo-Rodrigalvarez, A.; Serrano, J.; Martinez-Murillo, R. (Current Pharmaceutical Design, 2010)
Alzheimer's disease (AD) constitutes a progressive neurodegenerative disorder and the main cause of dementia. Numerous studies have focused on the pathogenic mechanism of AD to cure or prevent this devastating disease. But, despite recent advances, our understanding on the pathophysiology of this genetically complex and heterogeneous disorder is rather limited and treatment of the disease consists of medications to control the symptoms. Acetylcholinesterase inhibitors and N-methyl-D-aspartate (NMDA) receptor antagonists are the only available treatments recommended to manage the cognitive deficits caused by the disease. Therefore, the production of new drugs that may be able to cure the underlying cause of this chronic disease, not just the symptoms, is a matter of clinical interest. There is data implicating nitric oxide (NO) in the progression of the disease. The three isoforms of the NO-synthesizing enzyme (NOS) operate as central mediators of amyloid beta-peptide (Aβ) action, giving rise to elevated levels of NO that contributes to the maintenance, self-perpetuation and progression of the disease. Reducing Aβ production and the cholinergic deficit is a goal in the treatment of AD. In addition, a possible way to delay the progression of the illness must include a rationale design of enzyme inhibitors, subtype selective, targeting NOS isoforms implicated in damage to brain cells in AD. We are now presenting an overview regarding approved drugs for AD treatment and substances that although are not in use for the treatment of AD, including NOS inhibitors, may represent useful tools to unravel the pathophysiologic enigma of AD.
Keywords: Lipoic acid